Tora! Tora! Tora! - Williams, Elmo 1913-; Fleischer, Richard; Forrester, Larry. 1924-1988; Oguni, Hideo 1904-1996; Kirkushima, Ryuzo; Masuda, Toshio 1927-; Fukasaku, Kinji; Balsam, Martin 1919-1996; Yamamura, So 1910-2000; Cotten, Joseph 1905-1994; Mihashi, Tatsuya 1923-2004; Marshall, E. G. 1914-1998; et al. (20th Century Fox Home Entertainment, 1999)
A dramatization chronicling the bombing of Pearl Harbor from both the Japanese and American points of view.